Avaliação de híbridos de goiaba tailandesa (Psidium guajava) e araçá-amarelo (Psidium cattleianum) quanto à resistência ao nematoide Meloidogyne enterolobii - Pavanelli, Bárbara da Silva (Universidade Federal de São Carlos, 2025)
The production of guava (Psidium guajava) represents an agricultural activity of significant importance at the national level, presenting itself as an economically viable option for small and medium-sized farmers. In addition to being consumed fresh, guava is widely applied in industry. However, this crop faces relevant phytosanitary challenges, especially due to the gall nematode (Meloidogyne enterolobii), which causes severe damage to the root system, affecting the absorption of nutrients and decreasing productivity. One approach to overcome this obstacle is the development of varieties of resistant graft holders, such as the araçá-amarelo (Psidium cattleianum). The purpose of this study was to investigate the resistance of hybrids resulting from the crossing between Thai guava and yellow araçá in relation to the nematode M. enterolobii. Four hybrids (TAI x AA P0F2 2024, TAI x AA P0F2 2209, TAI x AA P1F2, TAI x AA P2F2) and the araçá-amarelo were examined, both in conditions with and without inoculation. The inoculation was performed using the sampling and analysis method proposed by Coolen & D'Herde (1972). The variables evaluated included: height and growth rate index of plants, chlorophyll a and b contents, fresh mass of the aerial part and roots, as well as final number of nematodes and number and index of galls. The experiment was carried out in a totally randomized way, containing five repetitions by varieties, in addition the data were expressed in means and subjected to the Scott-Knott clustering test with a significance level of 5%. The reproduction factor (RF) was determined by the equation FR = final population/initial population. The research findings showed that the araçá-amarelo has a remarkable resistance to the nematode M. enterolobii, since it reveals the lowest amount of nematodes per gram of root, in addition to having the lowest gall index and a reproduction factor (RF) close to zero. On the other hand, the hybrids analyzed showed a certain tolerance to the nematode, showing a RF lower than 1, which indicates a reduction in the reproduction of the parasite, although they did not achieve complete immunity. The study identifies the TAI x AA P0F2 2209 hybrid as the most promising option for future research in genetic improvement and nematode control, due to its robust growth and tolerance. In contrast, araçá-amarelo, despite its limited growth, shows resistance.
Evaluation of tailandesa guava (Psidium guajava) and araçá-amarelo (Psidium cattleianum) hybrids for resistance to the nematode Meloidogyne enterolobii
Keywords: Nematologia; Fruticultura; Fitossanidade; Goiabeira; Nematology; Fruit growing; Plant health; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA